2016
DOI: 10.1016/j.chemosphere.2016.02.059
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the levels and particle size distribution of lower chlorinated dioxin/furans (mono- to tri-chlorinated homologues) with those of tetra- to octa-chlorinated homologues in atmospheric samples

Abstract: h i g h l i g h t sSCl 1e3 DD/Fs accounted for 85% of SCl 1e8 DD/Fs in air samples. The mean concentration of SCl 1e3 DD/Fs was 5.4 times that of SCl 4e8 DD/Fs in the air. SCl 1e3 DD/Fs occurred mainly in the gas phase, and SCl 4e8 DD/Fs mainly in particles. SCl 1e3 DFs were the dominant form of SCl 1e3 DD/Fs in all particle size classes. t r a c tThere is very little information on the levels and particle size distributions of lower chlorinated dibenzop-dioxins and dibenzofurans (mono-to tri-CDD/Fs, SCl 1e3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…This is important for the assessment of the atmospheric fate, as it suggests a high long-range transport potential of these pollutants. The MSDs leaning toward the submicron size range highlight the significance of NPAHs' and OPAHs' inhalation exposure of also the deep lung, which is consistent with other aromatic combustion by-products like the parent PAHs, 79 PCDD/Fs, 98 and nitrated monoaromatics. 70 Particulate PAH and quinones are strong radical sources, in particular close to the combustion sources.…”
Section: Resultssupporting
confidence: 76%
“…This is important for the assessment of the atmospheric fate, as it suggests a high long-range transport potential of these pollutants. The MSDs leaning toward the submicron size range highlight the significance of NPAHs' and OPAHs' inhalation exposure of also the deep lung, which is consistent with other aromatic combustion by-products like the parent PAHs, 79 PCDD/Fs, 98 and nitrated monoaromatics. 70 Particulate PAH and quinones are strong radical sources, in particular close to the combustion sources.…”
Section: Resultssupporting
confidence: 76%
“…S5 ) indicated close combustion sources and are consistent with the possible influence of wood burning. The MSDs peaking in the sub-micrometre size range highlight the significance of NMAHs’ inhalation exposure of the deep lung (Kitanovski et al 2020 ), similar to other aromatic combustion byproducts like the parent PAHs (Ringuet et al 2012 ) and polychlorinated dibenzodioxins and -furans (Zhang et al 2016 ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the distributions of organic pollutants in PM fractions can be used to identify the sources, behaviors, and environmental fate of pollutants. Consequently, the size-specific distribution of organic pollutants in the atmosphere has been widely investigated, including polycyclic aromatic hydrocarbons (PAHs) (Duan et al 2007;Kiss et al 1998), polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs) (Chuang et al 2015;Oh et al 2002;Zhang et al 2016;Zhang et al 2015), PCBs (Chen et al 1996;, polychlorinated naphthalenes (PCNs) (Zhu et al 2016), organochlorine pesticides (Landlová et al 2014), polybrominated diphenyl ethers (Mandalakis et al 2009), hexabromocyclododecane (Okonski et al 2014), and tetrabromobisphenol A (Ni and Zeng 2013). Most of these studies showed that the pollutants tended to be concentrated in smaller particles.…”
Section: Introductionmentioning
confidence: 99%